Multi-component adsorption of Pb(II), Cd(II), and Ni(II) onto Egyptian Na-activated bentonite; equilibrium, kinetics, thermodynamics, and application for seawater desalination. Issue 1 (March 2016) - Taha, A.A.; Shreadah, Mohamed A.; Ahmed, A.M.; Heiba, Hany Fathy
Highlights: Competitive removal of Pb, Cd and Ni traces from a ternary ion solution. Structural characterization for Egyptian Na-activated bentonite. Wide variations in adsorption thermodynamics between the studied metals. Egyptian Na-activated bentonite can selectively remove Pb > Cd > Ni. Higher than 92% removal of Pb, Cd, Ni, Cu, Mn, Cr and Zn from polluted seawater. Abstract: The adsorption potential of the Egyptian Na-activated bentonite (Na-AB) to remove Pb(II), Cd(II), and Ni(II) from synthetic ternary-ion solutions and contaminated seawater, was investigated for the first time. In this study, natural Egyptian Ca-bentonite was activated to Na-AB, which then was characterized using XRF, XRD, FT-IR, and BET. The adsorption process was strongly influenced by pH, contact time, adsorbent dose, metal concentration, agitation speed, and temperature. The isotherm equations due to Langmuir and Freundlich isotherm models showed good fits with the experimental data. Na-AB has a Langmuir monolayer capacity in a decreasing order of; Pb(II) (5.43 mg/g) > Cd(II) (3.14 mg/g) > Ni(II) (2.77 mg/g), these are considered high capacity values relative to the initial concentration (10 mg/L of each metal). The adsorption selectivity was interpreted by means of atomic radii, charge density and hydration enthalpy. The multi-component adsorption kinetics was more accurately described by pseudo-second-order model. The intraparticle diffusion model gave multi-linear curves, so more than one-step controlled the adsorption process. Activation energy was calculated as 17.54, 13.73, and 28.66 kJ mol −1 for Pb(II), Cd(II), and Ni(II) respectively, suggesting physical adsorption. Thermodynamic parameters at different temperatures (290–328) K showed that (i) Pb(II) adsorption was spontaneous and exothermic, (ii) Cd(II) adsorption was non-spontaneous and endothermic, (iii) Ni(II) adsorption was non-spontaneous and exothermic. Application study on polluted seawater, showed removal efficiency within range of 92–100% not only for Pb(II), Cd(II), and Ni(II) but also for other co-existing metals like Cu(II), Mn(II), Cr(III), and Zn(II).